Application of Hybrid Contracts Concept in Factoring - Fauzan, Ihsan; Herdiana Abdurrahman, Nana; Prasetyo, Yoyok (Yayasan Mentari Madani, 2024)
In the business world, business people and companies always want to speed up their production of goods, so that they can increase profits and speed up capital turnover which in turn will encourage economic growth. With the increasing public demand for goods, this has resulted in the rise of many companies providing fresh funds or loan funds as capital obtained from factoring institutions. Factoring financing institutions are defined as business entities that carry out financing activities in the form of purchasing and/or transferring and managing short-term receivables. As an alternative for business funding, factoring is not as popular as other types of funding, even though this funding alternative is quite promising, especially at this time. The problem approach in this research uses a library study method which is carried out by collecting and analyzing several written works. The steps carried out in this literature study method are reducing data in the form of editing and summarizing in order to obtain main data regarding the essence related to factoring institution innovation (Factoring). The results of the research and discussion show that financing companies that provide receivable transfer services using the concept of factoring will make it easier for companies to settle their receivables and avoid unexpected risks such as default (broken promises) from other parties.